Practitioners' eye on continuous software engineering: an interview study - Johanßen, Jan Ole; Kleebaum, Anja; Paech, Barbara (Proceedings of the 2018 International Conference on Software and System Process (ICSSP '18), 2018)
Continuous software engineering (CSE) emerged as a process that is increasingly applied by practitioners. However, different perceptions of CSE among practitioners might impede its adoption in industry. We aim to support practitioners by giving a comprehensive overview of current CSE practices. Our observations provide guidance for practice on how to establish, assess, and advance CSE in their company. We conducted an interview study with 24 practitioners from 17 companies during 20 interviews. Following a semi-structured approach, we asked for their definition of CSE, most relevant elements for CSE, their experiences, and plans for further additions to their CSE process. From the practitioners' statements, we identified five perspectives on CSE and found tool- and methodology-driven definitions most prevalent. Automated tests, involved users, and a shared ruleset are perceived as most relevant for CSE. Practitioners' positive experiences with CSE are more frequent than negative ones; however, more than half of the responses were neutral. Practitioners' future plans focus on enhancement, expansion, and on-demand adaption of current practices. We conclude that CSE remains partially difficult to capture for practitioners. Therefore, we structure CSE in a model, the Eye of CSE.